Potential switchovers in comparative advantage: Patterns of industrial convergence - Michael Landesmann; Robert Stehrer (Johannes Kepler University of Linz, Department of Economics, 2000)
Although there exists a vast literature on convergence and divergence of income levels across countries or regions at the aggregate level, there is only little work on convergence and/or diver- gence processes of productivity and wage levels at the more disaggregated industrial level. These are especially important in the context of international trade as these determine the dynamics of comparative advantages and the resulting trade structures between developing and developed countries. In the first theoretical part, we discuss some theoretical aspects of uneven sectoral productivity and wage catching-up processes and their links to dynamic comparative advan- tages and trade structures. In the second part we present an econometric study of catching-up of wages, productivity, and labour unit costs. The analysis is conducted at the industrial level (ISIC 3-digit) over the period 1965-1995 for a set of catching-up economies compared to more advanced countries.
Keywords: F14; L6; O10; O14; O30; O41; 330; catching-up; comparative advantages; unit labour costs; convergence patterns; industrial development; Industrie; Lohnstückkosten; Entwicklungskonvergenz; Komparativer Kostenvorteil; Industriegüteraußenhandel; Internationaler Wettbewerb; Schätzung; Entwicklungsländer; Industriestaaten